Evolution of surgery of ventricular septal defect closure - Akkerbez Adilbekova; Shukhrat Marasulov; Bakhytzhan Nurkeyev; Saken Kozhakhmetov (National Scientific Medical Center, 2022)
A ventricular septal defect is one of the foremost prevalent congenital heart defects, accounting for around 20% of all congenital heart malformations. Nowadays, there are three surgical methods for ventricular septal defect: surgical treatment of ventricular septal defect with a heart-lung machine, interventional closure of ventricular septal defect by percutaneous puncture, and hybrid operation (with no heart-lung machine). Hybrid operation - there is some of the latest evolutions introduced in cardiac surgical treatment practice. This technique is mild, to reduce surgical trauma, and perform not connecting the patient to the heart-lung machine, without X-ray exposure, and there are additional indications than the interventional procedure. The article reviewed literature sources on the surgical treatments of the ventricular septal defect and the results of the above methods, and also considers more detail especially hybrid operation (without a heart-lung machine).